EXECUTIVE ALLOWANCES ON RISK TAKING AMONG THE LISTED COMMERCIAL BANKS IN KENYA - Njogu, Lucy Wanjiru; Gekara, Dr. Mouni; Waititu, Dr. Gichuhi A.; Omido, Dr. Karim (European Journal of Business and Strategic Management, 2017)
Purpose: The purpose of this study was to determine the effect of executive allowanceson risk taking among the listed commercial banks in Kenya. Methodology:The study used an Epistemology research philosophy, causal research design was adopted whereby panel data approach was used. The target population for this study were the 11 listed banks on the NSE. Secondary Data for the year 2010 to 2015 was collected from the NSE handbook. Data collected was analyzed using descriptive statistics which included means and standard deviations. Inferential statistics such as Pearson correlation and panel regression was also used. The results were presented in form of tables, figures, charts, graphs and trend lines. Results: The study findings revealed that Executive Allowances and risk taking were negatively and significantly related. Policy recommendation: The study recommended that banks should entice their staff with huge allowances as this will decrease risk.